2010
DOI: 10.1038/pj.2010.93
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of thermoresponsive unimolecular polymeric micelles with a hydrophilic hyperbranched poly(glycidol) core

Abstract: This paper describes the reversible phase transition behavior of a thermoresponsive poly(N-isopropylacrylamide) (PNIPAM) shell at the surface of a hydrophilic core. Reversible addition-fragmentation transfer (RAFT) polymerization of N-isopropylacrylamide was conducted using a hydrophilic hyperbranched poly(glycidol) (HPG)-based macroRAFT agent. At lower temperatures (o30 1C), the resultant multiarm star block copolymer (HPG-PNIPAM) exists as unimolecular micelles, with hydrophilic HPG as the core and a densely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 79 publications
0
27
0
1
Order By: Relevance
“…Luo et al [625] have described the preparation of poly (NIPAm) 'stars' from a hyperbranched poly(glycidol) (HPG)-based macro-RAFT agent prepared as shown in Scheme 26.…”
mentioning
confidence: 99%
“…Luo et al [625] have described the preparation of poly (NIPAm) 'stars' from a hyperbranched poly(glycidol) (HPG)-based macro-RAFT agent prepared as shown in Scheme 26.…”
mentioning
confidence: 99%
“…It has been reported that amphiphilic HPG derivatives can form unimolecular particles, which have smaller particle sizes compared with normal micelles formed by one molecule. This could be explained by their unique topologies, including their highly branched structures and spherical shapes . From dynamic light scattering results, as shown in Figure (A), we found that the size of HPG‐C18 aggregates was approximately 226.4 nm; these would be better called large aggregates rather than unimolecular particles.…”
Section: Resultsmentioning
confidence: 93%
“…In this study, a hyperbranched amphiphilic polyglycerol derivative (HPG) was synthesized and used for drug delivery. It has been reported that HPGs could form stable unimolecular micelles because of their unique topologies . HPGs also show excellent blood compatibility and have, therefore, been applied widely in biomedicine .…”
Section: Introductionmentioning
confidence: 99%
“…For example, hbPG with poly(N-isopropylacrylamide) arms, that exhibits thermoresponsive properties, have been described. 176 By combination of RAFT and ATRP, the synthesis of interesting miktoarms (polystyrene and poly(tert butyl acrylate)) on a hbPG core could be realized. 177 While hbPG represents a hydrophilic core for MSPs, the utilization of hyperbranched aliphatic polyethers based on 3-alkyl-3-(hydroxymethyl)oxetanes yields hydrophobic core structures.…”
Section: Multiarm Star Copolymers With a Hyperbranched Corementioning
confidence: 99%